Effect of progressive resistance training on health-related quality of life in the first year after breast cancer surgery – results from a randomized controlled trial. (4th May 2019) - Ammitzbøll, Gunn; Kristina Kjær, Trille; Johansen, Christoffer; Lanng, Charlotte; Wreford Andersen, Elisabeth; Kroman, Niels; Zerahn, Bo; Hyldegaard, Ole; Envold Bidstrup, Pernille; Oksbjerg Dalton, Susanne
Abstract: Aims: To examine the effect of progressive resistance training (PRT) on health related quality of life and a predefined symptom cluster of pain–sleep–fatigue. Methods: This study was a planned secondary analysis of a randomized controlled trial examining the effect of PRT on prevention of arm lymphedema in a population of women between 18 and 75 years undergoing breast cancer surgery with axillary lymph node dissection. Participants were allocated by computer randomization to usual care control or a PRT intervention in a 1:1 ratio. The intervention, initiated in the third post-operative week, consisted of three times PRT per week, supervised in groups in the first 20 weeks, and self-administered in the following 30 weeks. Questionnaire assessments were made at baseline, 20 weeks and 12 months, with the European Organization for Research and Treatment in Cancer Core questionnaire (EORTC QLQ C30) and the Functional Assessment of Chronic Illness Therapy-(FACIT) fatigue questionnaire. The symptom cluster of pain–sleep–fatigue was measured with a constructed score adding EORTC C30 subscales of insomnia, pain, and fatigue. Data were treated as repeated measurements and analyzed with mixed models. Results: Among 158 recruited participants, we found a clinically relevant increased emotional functioning with nine points at both follow-ups ( p  = .02), and 16 and 11 points at 20 weeks and 12 months respectively ( p  = .04) in social functioning. Furthermore, in the subgroup of women with the symptom cluster pain–sleep–fatigue present at baseline, a significant effect was found for global health status ( p  = .01) and social functioning ( p  = .02). Conclusion: To our knowledge, this is the first study to report clinically relevant effects of PRT on social and emotional functioning in the first postoperative year after breast cancer surgery. Furthermore, a subgroup of women with the pain–sleep–fatigue symptom cluster had particular benefit from PRT on global health status and social functioning.